Development Of A Small Tile Craft Industry In An Effort To Increase The Welfare Of Crawings In Islamic Economic Perspective - Firda Angelia Mutiara Pabeta; Hendri Hermawan Adinugraha (Journal of Islamic Economics and Business, 2023)
This study aims to analyze the development of the small tile craft industry in Pragak, Pekalongan Selatan, Pekalongan City, from the perspective of Islamic economics, with the primary goal of enhancing the welfare of craftsmen. Adopting a field research approach, the researcher directly engages with the industry and collects data to gain comprehensive insights into the existing challenges and potential solutions. The process of business development is viewed as a gradual and systematic means to improve the knowledge, skills, attitudes, and overall performance of those responsible for managing the craft industry. Central to this approach are key Islamic principles such as honesty, trust, friendliness, fairness, and patience, which guide the formulation and implementation of strategies that ensure mutually beneficial outcomes for all stakeholders involved. The study emphasizes the significance of aligning the tile craft industry's activities with the needs and aspirations of the community, contributing to humanitarian causes, and promoting prosperity within the society. By adhering to Islamic values and positively impacting the community, the small tile craft industry has the potential to thrive while fostering the well-being of craftsmen and society as a whole.